Is Health Contagious?—Based on Empirical Evidence From China Family Panel Studies' Data - Hu, Feng; Shi, Xiaojiao; Wang, Haiyan; Nan, Nan; Wang, Kui; Wei, Shaobin; Li, Zhao; Jiang, Shanshan; Hu, Hao; Zhao, Shuang (Frontiers in Public Health, 2021)
This study empirically analysed the contagion of health using data from China Family Panel Studies. We first controlled variables related to health behaviour, medical conditions, individual characteristics, household characteristics, group characteristics, and prefecture/county characteristics and then employed multiple methods for estimation. The estimates showed that the average health level of others in the community had a significant positive effect on individual self-rated health—health was contagious. The measurement results remained robust after the endogeneity of the core explanatory variables was controlled using two-stage least squares. Furthermore, by analysing the heterogeneity of health contagion, we found that the contagion effect of health varied with the level of medical care, household affiliation, gender, rural/urban areas, and age groups. The contagion effect of health was more pronounced in the elderly population and the rural areas of the central region, where the level of medical care is relatively low, whereas it did not differ significantly between genders. Finally, the learning or imitation mechanism and social interaction mechanism of health contagion were examined.